Anti-mycotoxin Effect and Antifungal Properties of Essential Oil from Ammodaucus leucotrichus Coss. & Dur. on Aspergillus flavus and Aspergillus ochraceus. Issue 1 (2nd January 2017) - Khaldi, Achraf; Meddah, Boumedien; Moussaoui, Abdellah; Sonnet, Pascal
Abstract: The essential oil of Ammodaucus leucotrichus Coss. & Dur. seeds growing wild in SouthWest of Algeria were obtained by hydrodistillation and analysed by GC and GC-MS. Other parameters such as density, refractive index, optical rotation, freezing point, solubility in ethanol, acid value and ester index are also measured. The antifungal properties of the essential oil were conducted using biomass technique on liquid medium, mycotoxigenic test, mycelial growth, determination of minimum inhibitory concentration (MIC), sporulation and germination spores'. The essential oil was found to be active against Aspergillus flavus MTTC 2799 (Microbial Type Culture Collection and Gene Bank) and Aspergillus ochraceus CECT 2092 (Spanish Type Culture Collection). The GC and GC-MS data showed a total of 19 compounds were identified in the hydrodistilled oil. The oil was dominated by oxygenated monoteprenes represented by perilla aldehyde (81.62%).